Quantifing trade barriers: Has protection declined substantially in Indian manufacturing? - Deb Kusum Das (Indian Council for Research on International Economic Relations (ICRIER), 2003)
This paper on Quantifying Trade Barriers: Has Protection Declined Substantiallyin Indian Manufacturing forms a part of a larger study on Productivity Growth and TradeRegimes: A study of Indian Manufacturing Industries in the 1980s and 1990s beingundertaken at ICRIER. This study is the first attempt at quantifying trade barriers at thelevel of disaggregate industry groups for Indian manufacturing for a period of 20 yearsstarting from the 1980s. The paper seeks to carry out this exercise to examine whetherprotection has indeed declined in Indian manufacturing.The study undertakes a quantification of trade barriers for Indian manufacturingindustries by examining both the tariff and the non-tariff barriers. It documents the tradebarriers for around 72 industries belonging to intermediate, capital and consumer goodssectors for period 1980-2000 and the phases of trade reforms therein. Our estimatessuggest levels of effective rate of protection and percentage of imports subject to licensing declined during the nineties while import penetration rates show an increaseonly in the second half of the nineties. This suggests that there may be considerable lagsbetween reduction of tariffs and non-tariff barriers and measurable impact on imports andon the economy
Keywords: 330